Pregnancy in Potts Disease: A Case Report and Review - Yusuf, N; Ali, MA; Ahmad, Q; Rahman, L; Nigar, T (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Spinal tuberculosis (Potts disease) during pregnancy reported to be rare & can be associated with destruction of the intervertebral disc & adjacent vertebrae that can lead to cord compression & thereby paraplegia or quadriplegia. Delay in diagnosis is common & most cases are diagnosed when paraplegia has already been occurred. This serious complication requires special attention during pregnancy & delivery. Here we reported a case of term pregnancy with Potts paraplegia. As the patient had complete motor & sensory loss from D7 level, (above the level of umbilicus to the lower limbs) LUCS was done without anesthesia & a healthy female baby was delivered. She did not require any analgesia post operatively DOI: http://dx.doi.org/10.3329/bjog.v25i1.13731 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 37-40